As práticas de transparência na execução orçamentária em Municípios da Região Metropolitana do Estado de São Paulo - Pascoaloto, Fabiana Ferreira (2018)
This research aims to analyze if Metropolitan Region of Sao Paulo municipalities meet requirements established by the Complementary Law 131/2009 in relation to compliance of minimum regulatory requirements in their official websites, as well as information service timeliness. In order to build the assessment form and content analysis of municipality official website it was used the bibliographical research. The study has also explored if transparency practices are in accordance to Brazilian legislation, which determine the need to accountability in the national public management. The investigation focuses on the disclosed information by thirty-nine Metropolitan Region of Sao Paulo municipalities and transparency official websites, with respect to compliance with the wide dissemination in official websites for public access to information. The measurement was performed in the acts practiced by the management units in the course of budget execution of the public revenue and expenditure and on the disclosure timeliness. To conclude it was detected the scenario in which the municipalities are in this transparency process and legal assistance